(untitled) (Bangladesh Journal of Child Health, 2019)
Underdevelopment of lung is a group of congenital anomalies classified into agenesis, aplasia, and hypoplasia of lung, on the basis of presence or absence of lung parenchyma, bronchial tree, and pulmonary artery. The pathogenesis of such anomalies is not accurately known with several proposed theories. It is often associated with anomalies of the cardiovascular & genitourinary systems. An isolated left upper lobe pulmonary agenesis is rare and more commonly involves the right upper and middle lobes. The prevalence of this condition has been noted to be 0.0034–0.0097%. It is associated with the absence of lung parenchyma, bronchial tree, pulmonary vasculature, and may remain undiagnosed until adulthood. Treatment depends on patient’s symptoms, with most patients being treated conservatively. Herein, we report an eight month old infant who presented with fever, cough, and respiratory distress and treated as a case of left sided pneumonic collapse consolidation without radiological improvement and finally diagnosed as a case of left upper lobe pulmonary agenesis with low serum IgA level. Bangladesh J Child Health 2019; VOL 43 (2) :122-125